1981
DOI: 10.1071/pp9810093
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of Sugars to Osmotic Adjustment in Elongating and Expanded Zones of Wheat Leaves During Moderate Water Deficits at Two Light Levels

Abstract: Water was withheld from wheat seedlings grown at two light levels, so that the soil water content was reduced by 50% and the leaf water potential of treated plants was about 0.5 MPa below that of controls. Growth was initially reduced but recovered after about 4 days of the water deficit treatment. Osmotic adjustment (calculated as the difference between the osmotic potential at 100% relative water content of the treated and controls plants) occurred in both the elongating and expanded zones of leaves. In plan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
89
0
3

Year Published

1991
1991
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 178 publications
(102 citation statements)
references
References 12 publications
8
89
0
3
Order By: Relevance
“…NL also enhanced the activity of invertase in MvTD10-10 under both water regimes, which reflects its light dependency. A higher level of sucrose hydrolysis was also found in water-stressed wheat plants under NL (Munns and Weir, 1981). In this connection, it seems that both mild water deficiency and NL are able to compensate for the reducing effect of cold on sugar remobilisation in these durum cultivars via the higher activity of invertase.…”
Section: Discussionmentioning
confidence: 63%
“…NL also enhanced the activity of invertase in MvTD10-10 under both water regimes, which reflects its light dependency. A higher level of sucrose hydrolysis was also found in water-stressed wheat plants under NL (Munns and Weir, 1981). In this connection, it seems that both mild water deficiency and NL are able to compensate for the reducing effect of cold on sugar remobilisation in these durum cultivars via the higher activity of invertase.…”
Section: Discussionmentioning
confidence: 63%
“…Kerepsi and Galiba (2000) reported that carbohydrates changes are important because of their relationship with such physiological processes as photosynthesis, translocation and respiration. Some studies reported that plants sugars content rose (Munns and Weir 1981) or remained constant (Morgan 1992) under salinity.…”
Section: Resultsmentioning
confidence: 99%
“…Drossopoulos, Karamanos & Niavis (1987) compared irrigated and rainfed wheat and found that sucrose accumulated in laminae under stress whereas monosaccharide contents were low and unaffected. On the other hand, Munns & Weir (1981) exposed pot-grown wheat plants to moderate water stress over periods of several days and found that glucose was the predominant sugar in the leaves, and accumulated most rapidly during drought. Riazi, Matsuda & Arslan (1985) described yet another pattern of response when barley seedlings were exposed to brief (up to 7 h) osmotic stress: sucrose contents decreased and glucose increased.…”
Section: Adaptation To Droughtmentioning
confidence: 99%